Expanding the Organometallic Chemistry of 4d and 4f Arene Metal Complexes - Bamforth, Christopher (Université d'Ottawa / University of Ottawa, 2022)
Organometallic chemistry is a discipline which grants sophisticated control over metal ions’ electronic properties, facilitating the design of materials with tailorable physical properties. Chapter 1 gives an overview of organometallic chemistry, with a focus on transition metal and lanthanide π-bonded systems, and an introduction to ligand Field theory and molecular magnetism. In Chapter 2, the magnetic and fluorescent characterisation of the dysprosium (III)piano-stool complex, [DyCp*(BH4)2(THF)], and its borodeuteride congener,[DyCp*(BD4)2(THF)], are described. Analysis of these results shows that the relatively low-symmetry complexes show slow magnetic relaxation via a through-barrier mechanism, because of the strong crystal field imposed by the Cp* Ligand. Computational methods were utilised to show that the bonding in these complexes has significant covalent character, contrary to the classical view of 4f bonding. In Chapter 3, we discuss the organometallic chemistry of palladium cyclobutadiene complexes, and report the synthesis and structural characterisation of the zerovalent palladium metallocene [Pd(C4Ph4)2], the first structurally-authenticated tetraphenyl cyclobutadiene metallocene. In Chapter 4, we discuss the use of asymmetric alkynesto synthesise cis and trans isomers of bisphenylbis trimethylsilyl) cyclobutadienediide (Cb), for which the organometallic chemistry is hitherto unreported. The reactivity of these salts with lanthanide ions was explored for the first time. We report two structurally authenticated coordination polymers, varying by ratio of Li:BH4 ions within the lattice. In Chapter 5, we discuss the synthesis of the dysprosium (III) 9-borabicyclononane hydroborate THF solvate,[K(THF)6][Dy(HBBN)2(THF)2], and its reactivity with the aforementioned lithium cyclobutadienediide salts. We report two complexes, [Dy(HBBN)2(THF)(μ-Cbtrans)Li(THF)].[Dy(HBBN)2(THF)(μ-Cbtrans)K(THF)]4 and their structural investigation. Chapter 6 describes the exploratory chemistry of the Cb salts described previously for the future development of multinuclear SMMs and perspectives on the organometallic chemistry presented
Keywords: Organometallic; inorganic; magnetochemistry; 4f; 4d; arene; cyclobutadiene; cyclopentadiene